Analytical performance of nano‐LC‐SRM using nondepleted human plasma over an 18‐month period. Issue 15 (25th July 2016) - Song, Xiaomin; Amirkhani, Ardeshir; Wu, Jemma X.; Pascovici, Dana; Zaw, Thiri; Xavier, Dylan; Clarke, Stephen J.; Molloy, Mark P.
Abstract : A standardized procedure for label‐free nano‐LC‐SRM analysis of 32 high‐medium abundance proteins from nondepleted human plasma was established and SRM data were acquired on 45 separate days for a control sample that was independently prepared on 39 distinct dates over an 18‐month period (542 days). This case study enabled us to assess quantitative variance associated with nano‐LC‐SRM plasma analysis, mimicking experimental conditions that would be experienced with clinical trial biomarker studies. We assessed sample preparation variability attributed to different technicians and sample storage stability. Instrument performance varied over the 18‐month period requiring ion path cleaning, so we assessed the impact of declining performance on specific peptide ion sensitivity and evaluated how various data normalization strategies could compensate for these changes. Our analysis demonstrated that while sample preparation was the main contributor for data variances when MS data were acquired within days, variability in SRM sensitivity was a far greater source of variance when data were acquired over a long period. The overall median multiplexed assay CV was 13% over the 18‐month period. This case study is illustrative of large‐scale plasma biomarker studies using nano‐LC‐SRM over extended periods and highlights aspects of bioanalysis that require careful attention to ensure reliable quantitation.